Credit Allocation and Financial Crisis in Korea - Borensztein, Eduardo; Lee, Jong-Wha. (Washington, D.C. : International Monetary Fund, 1999)
This paper analyzes some of the structural problems associated with the Korean financial sector, and investigates whether the financial system has allocated credit in an efficient way over the past three decades. Using data for 32 manufacturing sectors, we find no evidence that credit flows were directed to the relatively more profitable sectors, either before or after the financial reforms. We also find that the flow of credits did not contribute to improve the economic performance of the favored industries over time.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet